Eco-Friendly Enzyme Production: Utilizing Invasive Wedelia trilobata L. for Cellulase Synthesis with Aspergillus niger - Rajappan, Rejitha Lalitha; Skaria, Chacko Suju (Asian Journal of Biological and Life Sciences, 2025)
Aim: This study explores Wedelia trilobata as a substrate for cellulase production by Aspergillus niger via Solid-State Fermentation and evaluates antibacterial activity of its extracts. Materials and Methods: SSF was performed and cellulase quantified using DNS; antibacterial activity assessed by well diffusion. Results: Maximum enzyme activity observed at 120 hr; protein peaked at 831 µg/mL. Antibacterial assays showed highest inhibition 15 mm against E. coli. Conclusion: Wedelia trilobata is a viable substrate for cellulase production and a source of antibacterial compounds, offering eco-friendly applications.
Keywords: Wedelia trilobata; Cellulase; Solid-State Fermentation; Antibacterial